H3Africa and the African Life Sciences Ecosystem: Building Sustainable Innovation - Dandara, Collet (OMICS, 2014)
Interest in genomics research in African populations is experiencing exponential growth. This enthusiasm stems in part from the recognition that the genomic diversity of African populations is a window of opportunity for innovations in postgenomics medicine, ecology, and evolutionary biology. The recently launched H3Africa initiative, for example, captures the energy and momentum of this interest. This interdisciplinary socio-technical analysis highlights the challenges that have beset previous genomics research activities in Africa, and looking ahead, suggests constructive ways H3Africa and similar large scale science efforts could usefully chart a new era of genomics and life sciences research in Africa that is locally productive and globally competitive. As independent African scholars and social scientists, we propose that any serious global omics science effort, including H3Africa, aiming to build genomics research capacity and capability in Africa, needs to fund the establishment of biobanks and the genomic analyses platforms within Africa. Equally they need to prioritize community engagement and bioinformatics capability and the training of African scientists on these platforms. Historically, the financial, technological, and skills imbalance between Africa and developed countries has created exploitative frameworks of collaboration where African researchers have become merely facilitators of Western funded and conceived research agendas involving offshore expatriation of samples. Not surprisingly, very little funding was allocated to infrastructure and human capital development in the past. Moving forward, capacity building should materialize throughout the entire knowledge co-production trajectory: idea generation (e.g., brainstorming workshops for innovative hypotheses development by African scientists), data generation (e.g., genome sequencing), and high-throughput data analysis and contextualization. Additionally, building skills for political science scholarship that questions the unchecked assumptions of the innovation performers be they funders, scientists, and social scientists, would enable collective innovation that is truly sustainable, ethical, and robust.